The effect of the neutral cytidine protonated analogue pseudoisocytidine on the stability of i-motif structures - B. Mir (Nature Portfolio, 2017)
Abstract Incorporation of pseudoisocytidine (psC), a neutral analogue of protonated cytidine, in i-motifs has been studied by spectroscopic methods. Our results show that neutral psC:C base pairs can stabilize i-motifs at neutral pH, but the stabilization only occurs when psC:C base pairs are located at the ends of intercalated C:C+ stacks. When psC occupies central positions, the resulting i-motifs are only observed at low pH and psC:C+ or psC:psC+ hemiprotonated base pairs are formed instead of their neutral analogs. Overall, our results suggest that positively charged base pairs are necessary to stabilize this non-canonical DNA structure.